Comparison of lignin extraction processes: Economic and environmental assessment. (August 2016) - Carvajal, Juan C.; Gómez, Álvaro; Cardona, Carlos A.
Highlights: Four different lignin production processes are evaluated and compared. Economic and environmental technical evaluations are performed. Importance of the quality of lignin for high value-added products. Abstract: This paper presents the technical–economic and environmental assessment of four lignin extraction processes from two different raw materials (sugarcane bagasse and rice husks). The processes are divided into two categories, the first processes evaluates lignin extraction with prior acid hydrolysis step, while in the second case the extraction processes are evaluated standalone for a total analysis of 16 scenarios. Profitability indicators as the net present value (NPV) and environmental indicators as the potential environmental impact (PEI) are used through a process engineering approach to understand and select the best lignin extraction process. The results show that both economically and environmentally process with sulfites and soda from rice husk presents the best results; however the quality of lignin obtained with sulfites is not suitable for high value-added products. Then, the soda is an interesting option for the extraction of lignin if high quality lignin is required for high value-added products at low costs.